Media Workbook Fun-Math Interaktif Untuk Mitigasi Matematika Panti Asuhan Yauma - Agnesia, Varisca; Suryaningtyas, Wahyuni; Zainubah, Aluf; Mahiroh, Ana Hilmi (Journal Of Human And Education (JAHE), 2024)
This Community Service is focused on mentoring and training to improve children's learning abilities and interest in mathematics, especially children at the Yauma Orphanage, Surabaya. The determination of this assistance was motivated by the low interest and ability of foster children in science material, namely mathematics. Apart from that, the lack of learning facilities and inadequate educators make students less enthusiastic about developing their abilities because academic appreciation is rarely given. The objectives to be achieved from this community service PKM activity include: 1) efforts to help improve the learning abilities and interest of children at the Yauma Orphanage in understanding mathematics material, 2) providing education on how to understand fractions and shapes in everyday life , 3) fostering collaboration with partners, namely the Yauma Orphanage to introduce Interactive Fun-Math Workbook learning media. The method used to achieve the goals of this community service PKM is through training and mentoring for foster students at the Yauma Orphanage. Several components that were successfully achieved in implementing this activity included: 1) achieving the activity objectives, 2) achieving the material targets that had been planned for the Yauma Orphanage students.